Islamic Worldview sebagai Kritik terhadap Sekularisasi Ilmu Pengetahuan Modern - Ahmad Saad Nurifai; Sumiran Sumiran (TSAQOFAH, 2026)
The secularization of modern science has produced a dichotomy between science and religion, resulting in the reduction of metaphysical, ethical, and spiritual dimensions in the development of knowledge. This condition demonstrates the need for an epistemological paradigm capable of integrating revelation, reason, and empirical experience proportionally. This study aims to analyze the concept of the Islamic worldview as a critique of the secularization of modern science and to explain its relevance in developing an integrative scientific paradigm. This study employed a qualitative approach using the library research method. Data were obtained from the Qur’an, hadith, the works of contemporary Muslim thinkers, reputable scholarly articles, and academic literature related to the philosophy of science, Islamic epistemology, and secularization. The data were analyzed using content analysis techniques and critical analysis of various emerging scientific perspectives. The findings show that the Islamic worldview offers a scientific paradigm based on the principles of tawhid, the integration of revelation and reason, the unity of reality, and moral responsibility in scientific activities. This paradigm critiques secular assumptions that separate religion from science and affirms that knowledge functions not only as a rational-empirical instrument but also as a means to realize human welfare and devotion to Allah. The conclusion of this study indicates that the Islamic worldview makes a significant contribution to reconstructing the epistemology of modern science toward a system of knowledge that is holistic, ethical, and transcendental. The implications of this study provide a conceptual foundation for the development of higher education, scientific research, and academic policy based on the integration of knowledge with Islamic values.